Revisión documental sobre los trastornos de la salud mental en Bomberos voluntarios - Isaza Londoño, Nini Joana (Universidad Antonio Nariño, 2021)
This research is based on a documentary review on mental health-related disorders in Spanish-speaking volunteer firefighters, aged between 35 and 40 years.